Poetic purposes in the potry of Andalosian women until Almohad era. - Hattaa, Slman; Sliman, Nabil; Syrafe, Yaser Ahmad (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Andalusian women were able to go out to life and participate in all areas of life، women were imitating the molds of male pots in a different fashion. This study attempts to show women’s literature and role and to prove their creativity as men, it also seeks to refer to the new meanings added by women away from the meaning touched by men through the overlap of potic purposes each other.